What's behind a name? - Manova-Georgieva, Yana (ELOPE (Ljubljana), 2020)
Nominative symbolism in fantasy is a tool to attribute certain traits to literary characters and thus to convey meaning which enriches the readers' comprehension of the fictitious personality. Proper names in the English naming tradition are not generally seen as means of alluding to the character of a person, yet they have sometimes been chosen purposefully by writers so as to reveal the idea that a symbolic name tries to convey. The paper therefore aims at investigating the origin and author's intended meaning behind the names of some recurrent literary characters in Terry Pratchett's Discworld series from the viewpoint of their structure and the allusions they evoke in the reader's imagination. The analysis includes five names presenting three different structures: neologisms based on syntactic composition, imitations of borrowed structures that are foreign to the English model of naming, and typical English naming models where name symbolism is due to the lexical choice of the components in the name.
Keywords: karaktonimi; književna imena; književna onomastika; lastna imena; nanašanje; onomastika